Penggunaan Onggok sebagai Sumber Energi dalam Ransum Sapi - S.N.O. Suwandyastuti; Efka Aris Rimbawanto (Jurnal Agripet, 2012)
The utilization of cassava meal residues as energy source in dairy cows rationABSTRACT. The dairy farmer in the rural village, usually use rice brain and coconut meat kernels as the energy source, although coconut meat kernels is less palatable and too expensive. It is, therefore, important to seek for the other materials which are locally available and inexpensive. An experiment had carried out, using five lactating dairy cows in a Change Over Design as long as five periods. Each period lasted for 21 days, consisted of 14 days preliminary and seven days observation period. The animal function as column and the period as row, so that its 5 x 5 Latin Square. The treatment tested are five substitution levels of coconut meat kernels by cassava meal residues of 5, 7.5, 10, 12.5 and 15 percent dry matter ration respectively. The variables measured were : (1) ration digestibility and essential minerals balance; (2) daily milk production and milk composition; (3) rumen fermentation product. Based on the analysis of variance of all variables measured the experiment suggested that cassava meal residues can be used as the energy source to substitute coconut meat kernels in kernels in lactating dairy cattle ration of 5 up to 15 percent dry matter ration, without causing physiological disorder moreover, increases the milk composition.